NT-proBNP and sRAGE levels in early rheumatoid arthritis. (4th May 2023) - Heslinga, M; Teunissen, C; Agca, R; van der Woude, D; Huizinga, TWJ; van Laar, J; den Broeder, A; Lems, W; Nurmohamed, M
Abstract : Objective: Several biomarkers of cardiovascular function are found to be increased in rheumatoid arthritis (RA), with some suggesting a relationship with disease activity and improvement with adequate anti-rheumatic treatment. Promising biomarkers include N-terminal pro-brain natriuretic peptide (NT-proBNP) and the soluble receptor form of advanced glycation end-products (sRAGE). The objective of this study was to investigate associations between NT-proBNP and sRAGE levels and markers of inflammation and disease activity in early RA patients and their changes during (effective) anti-rheumatic treatment. Method: Data from 342 consecutive early RA patients participating in the 'Parelsnoer' cohort were used. At baseline and after 6 months' disease activity, NT-proBNP and sRAGE levels were assessed. Results: After 6 months, NT-proBNP decreased from 83 pmol/L (mean) at baseline to 69 pmol/L at follow-up (p < 0.001), while sRAGE increased from 997 pg/mL to 1125 pg/mL (p < 0.001). A larger decrease in erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) was associated with larger changes in NT-proBNP and sRAGE. For every point decrease in ESR, there was a 1.7-point decrease in NT-proBNP and a 2.2-point increase in sRAGE. For CRP, these values were 1.7 and 2.7, respectively (p < 0.001). Conclusion: Suppressing inflammation, independently of achieving remission, increases sRAGE levels and decreases NT-proBNP levels significantly. Whether this translates into a decrease in incident cardiovascular disease remains to be elucidated.